Analysis of the losses due to grapevine leafroll disease in Albariño vineyards in Rías Baixas (Spain) - Cabaleiro,Cristina (2013)
Leafroll disease symptoms in grapevine white varieties are milder than in red ones and producers do not regard leafroll to be economically significant especially when yield is not consistently affected. However, the potential alcoholic degree (PAD) of Albariño grapes from Grapevine leafroll associated virus 3 (GLRaV-3) infected plants in two vineyards in Rías Baixas (Spain), was found to be an average of 1º lower than the virus free ones. To analyse the economic losses, two price scales and six vintages for each location were used: A) Grape Purchase Agreements (GPA) and B) bonuses or penalties depending on mean PADs of each year. Income was 8.7% lower with (A) and 13% lower with (B), that is more than 2000 ha-1 per year. Annual and accumulated losses during the 30 years of vineyard lifespan, with 5% discount rate, and an average yield of 10 tha-1 were calculated for three scenarios: leafroll free vineyard (E1), 25% GLRaV-3 infected vineyard (E2) and vineyard leafroll free at planting and with mealybug vectors spreading GLRaV-3 up to 100% in 15 years (E3). In the E2 scenario the total income losses amounted to be in A) of 12.9% and in B) of 19.6% when compared to E1. In the E3 scenario the losses will be in A) 24.1% and in B) of 35.1% when compared with E1. These decreases in income in E3 could amount to 74,000 ha-1. This study confirms the need to stress the importance of taking GLRaV into consideration also in white varieties with no visible damages.